2017
DOI: 10.1039/c6fo01559j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gut microbiota and increase in fecal water content in mice induced by administration of Lactobacillus kefiranofaciens DN1

Abstract: Lactobacillus kefiranofaciens is the key probiotic bacterium in kefir. In this study, we investigated the effects of oral consumption of L. kefiranofaciens on the fecal quality and intestinal microbiota of mice. Four-week-old Balb/c mice were divided into two groups (n = 8 each) and administered 0.2 mL of saline (control group) or saline containing 2 × 10 cfu L. kefiranofaciens DN1 (LKF_DN1 group) for two weeks. At the end of the experiment, their fecal samples were collected and the fecal quality and microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…This supports the finding that L. kefiranofaciens supplementation ameliorated depressive-like behaviors in chronic-stressed mice by regulating gut microbiota content, which included the decreased abundance of Proteobacteria, a phylum that includes pathogens such as Salmonella (Sun et al, 2019). Other mice studies also supported the role of L. kefiranofaciens in modulating gut microbiota composition (Jeong et al, 2017b;Xing et al, 2018). Collectively, these changes in gut microbiota profile prevent gut dysbiosis that could lead to chronic inflammation, HPA axis overactivity and depression (Jeong et al, 2017b).…”
Section: Exopolysaccharide Peripheral Inflammation and Gut Microbiotasupporting
confidence: 73%
“…This supports the finding that L. kefiranofaciens supplementation ameliorated depressive-like behaviors in chronic-stressed mice by regulating gut microbiota content, which included the decreased abundance of Proteobacteria, a phylum that includes pathogens such as Salmonella (Sun et al, 2019). Other mice studies also supported the role of L. kefiranofaciens in modulating gut microbiota composition (Jeong et al, 2017b;Xing et al, 2018). Collectively, these changes in gut microbiota profile prevent gut dysbiosis that could lead to chronic inflammation, HPA axis overactivity and depression (Jeong et al, 2017b).…”
Section: Exopolysaccharide Peripheral Inflammation and Gut Microbiotasupporting
confidence: 73%
“…Probiotic candidates have been routinely screened based on their ability to survive in an artificial host barrier system such as with stimulation of gastric acid or enzymatic stresses [4]. In this study, we assessed novel aspects in probiotic screening using an experimental oral environment, including resistance against ambivalent atmospheric conditions in a survival assay and enzymatic action towards utilization of sucrose and acid production, which are linked to the development of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are thought to be exerted via enhancement of intestinal functions or inhibition of metabolic diseases caused by intestinal dysbiosis [3,4]. Despite the fact that the oral cavity is the first point of contact between probiotics and the host system [5], few studies have directly investigated the effects of probiotics on the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kefir has been associated with various health benefits through examining the mechanisms (Liu et al, 2012). According to several studies, Kefir had demonstrated ACE inhibitory activity, the ability to improve levels of serum cholesterol, and immunomodulatory characteristics, and so on (Maeda et al, 2004;Jeong et al, 2017). Additionally, among various lactic acid bacteria contained kefir, Lactobacillus kefiri, L. kefiranofaciens, and L. kefiranofaciens had shown beneficial effects for health in vivo (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%